Coulomb breakup of neutron-rich 29, 30Na isotopes near the island of inversion. (21st February 2017) - Rahaman, A; Datta, Ushasi; Aumann, T; Beceiro-Novo, S; Boretzky, K; Caesar, C; Carlson, B V; Catford, W N; Chakraborty, S; Chartier, M; Cortina-Gil, D; Angelis, G De; et al.
Abstract: First results are reported on the ground state configurations of the neutron-rich 29, 30 Na isotopes, obtained via Coulomb dissociation (CD) measurements. The invariant mass spectra of these nuclei have been obtained through measurement of the four-momenta of all decay products after Coulomb excitation of those nuclei on a 208 Pb target at energies of 400–430 MeV/nucleon using the FRS-ALADIN-LAND setup at GSI, Darmstadt. Integrated inclusive CD cross-sections (CD) of 89 (7) mb and 167 (13) mb for one neutron removal from 29 Na and 30 Na, respectively, have been extracted up to an excitation energy of 10 MeV. The major part of one neutron removal, CD cross-sections of those nuclei populate the core, in its ground state. A comparison with the direct breakup model, suggests the predominant occupation of the valence neutron in the ground state of 29 Na ( 3 / 2 + ) and 30 Na ( 2 + ) is the d -orbital with a small contribution from the s -orbital, which are coupled with the ground state of the core. One of the major components of the ground state configurations of these nuclei are 28 Na gs ( 1 + ) ⨂ ν s, d and 29 Na gs ( 3 / 2 + ) ⨂ ν s, d, respectively. The ground state spin and parity of these nuclei obtained from this experiment are in agreement with earlier reported values. The spectroscopic factors for the valence neutron occupying the s and d orbitals for these nuclei in the ground state have been extracted and reported for the first time. A comparison of the experimental findings with shell model calculation using the MCSM suggests a lower limit of around 4.3 MeV of the sd – pf shell gap in 30 Na.